Structural basis of transcription-coupled RNA damage by incorporation of oxidized ribonucleotides - Peini Hou; Chanjoo Lee; Jenny Chong; Juntaek Oh; Dong Wang (Proceedings of the National Academy of Sciences, 2026)
Oxidative stress induces damage to DNA, RNA, and nucleotide pools. Unlike well-studied DNA damage, the formation of RNA damage and the impact of an oxidized ribonucleotide pool on transcription fidelity are poorly understood. Here, we investigate the structural basis of transcription-coupled RNA damage and the effect of 8-oxo-guanosine triphosphate (8-oxo-rGTP) on RNA polymerase II (Pol II) transcription fidelity control steps. We revealed that the incorporation efficiency of 8-oxo-rGTP opposite a dC template is comparable to that of GTP. In contrast, the incorporation efficiency of 8-oxo-rGTP opposite a dA template is ~150-fold more efficient than that of GTP. For the extension step, Pol II extends substantially faster from a 3′-8-oxo-rG:dC base pair than from a 3′-8-oxo-rG:dA base pair. For the proofreading step, strikingly, Pol II EC with 3′-8-oxo-rG:dA base pair is much more resistant to backtracking and proofreading than Pol II EC with 3′-8-oxo-rG:dC base pair. Using X-ray crystallography, we revealed that 8-oxo-rGTP adopts different prechemistry binding sites depending on whether it is paired with a dC or a dA template. Upon incorporation, the nucleobase of 8-oxo-rG flips to the syn -conformation to form a Hoogsteen pair with a dA template, whereas it remains in the anti -conformation to form a Watson–Crick pair with a dC template. Collectively, our work demonstrates that nucleotide-pool oxidation can directly affect Pol II fidelity control steps and elongation dynamics and induce RNA damage in a transcription-coupled manner.